Contrasting microbial biogeographical patterns between anthropogenic subalpine grasslands and natural alpine grasslands. Issue 3 (7th October 2015) - Geremia, Roberto A.; Pușcaș, Mihai; Zinger, Lucie; Bonneville, Jean‐Marc; Choler, Philippe
Summary: The effect of plant species composition on soil microbial communities was studied at the multiregional level. We compared the soil microbial communities of alpine natural grasslands dominated by Carex curvula and anthropogenic subalpine pastures dominated by Nardus stricta . We conducted paired sampling across the Carpathians and the Alps and used Illumina sequencing to reveal the molecular diversity of soil microbes. We found that bacterial and fungal communities exhibited contrasting regional distributions and that the distribution in each grassland is well discriminated. Beta diversity of microbial communities was much higher in C. curvula grasslands due to a marked regional effect. The composition of grassland‐type core microbiomes suggest that C. curvula, and N. stricta to a lesser extent, tend to select a cohort of microbes related to antibiosis/exclusion, pathogenesis and endophytism. We discuss these findings in light of the postglacial history of the studied grasslands, the habitat connectivity and the disturbance regimes. Human‐induced disturbance in the subalpine belt of European mountains has led to homogeneous soil microbial communities at large biogeographical scales. Our results confirm the overarching role of the dominant grassland plant species in the distribution of microbial communities and highlight the relevance of biogeographical history.